Pengaruh Sustainability Report, Profitabilitas dan Leverage Terhadap Nilai Perusahaan pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Andini Nurmala Sari; Erika Takidah; Susi Indriani (Indo Publishing, 2025)
This study aims to determine (1) the influence of Sustainability Report disclosure on Company’s Value, (2) the influence of Profitability on Company’s Value, (3) the influence of Leverage on Company’s Value, (4) and the influence of Sustainability Report disclosure, profitability and leverage on Company’s Value. The research method uses an annual report and sustainability report with Random Effect Model (REM) method in the panel regression data analyzed with Eviews version 12 program. The population in this study is 24 mining companies listed on the Indonesia Stock Exchange period 2021-2023. The sample in this study is 21 mining companies from the purposive sampling method. The result of this study indicate Sustainability Report disclosure has negative influence on Company’s Value, (2) Profitability has positive influence on Compan’s Value, (3) Leverage has positive influence on Compan’s Value (4) and Sustanability Report, Profitability and Leverage have a simultaneously positive effect on Company’s Value